Positive effect of magnetism on cerebral malaria (A hypothesis) - Sugeng Juwono Mardihusodo Sugeng Juwono Mardihusodo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Cerebral malaria (CM) is one of serious complications of falciparum malaria that may cause high mortality rate in a malaria endemic area where Plasmodium falciparum is predominant. Based on a lot of histopathological findings, pathogenesis of CM is thought to be mainly caused by the blockade of cerebral vessels by parasitized red blood cells (PRBC), that could be aggravated by secondary factors such as depositions of immune complexes in brain capillaries, reduced humoral or cell-mediated immune responses, action of endotoxin, and the action of tumor necrosis factor (TNF). Biological effects of magnetism have been extensively and intensively studied in the past five decades including their applications to the treatment of common diseases. Among other conclusions reached by scientists after innumerable experimentations in the field of biomagnetism are (1) living systems are very sensitive to magnetic fields and magnetic effect reaches every cells in the body on account of the highly pervasive character of magnetism; (2) as the entire body is infused with electrical energy and magnetic fields exist in every part of it, magnets, if properly applied exercise a positive effect on the electrical response behaviour pattern; (3) effects on the blood picture and on erythrocyte sedimentation rate result, from exposure of the organism to a constant magnetic field which initiate biochemical changes; (4) a magnetic field can exert direct influence on the diencephalon and the forebrain. Studies on the effect of magnetism on blood revealed the activation of the iron content in the blood and a weak current was discerned to have been generated, the process of ionisation was hastened which freed the blood from danger of clotting and stimulated easier and more spontaneous flow of blood through the blood vessels and capillaries. It is hypothesized, therefore, that magnetism exerts a positive effect on CM.Key Words : magnetotherapy - biomagnetism - biomagnetics - malaria - biomagnetology